Do people get used to insulting language? - Struiksma, Marijn (Utrecht University, 2022)
This folder contains all information regarding the experimental set-up, data, analysis, and publication of the experiment on insulting and complimenting language in the brain. More detailed information can be found in the readme.txt and in the paper "Do people get used to insulting language? by Marijn E. Struiksma, Hannah De Mulder N.M. , & Jos J.A. van Berkum.
Keywords: Humanities - Languages and literature (6.2); Psycholinguistics; communication; emotion; insults; morality; EEG; ERP; skin conductance